Unveiling the reaction process of the amine in direct amidation of aromatic ketones in H2O. Issue 10 (7th October 2020) - He, Fangjun; Qu, Rumeng; Su, Jie; Du, Muyao; Liu, Junqiang; Chen, Yiping; Wang, Bo
Abstract: In the classical amidation between aromatic ketones and amines, 2.0 equivalents of amines are necessarily required to gain satisfying yields. The specific role of the amine in the direct amidation already puzzled us for a long time. In this work, we disclosed that the amine acts as both reactant and catalyst. Specifically, the determination of reaction intermediates revealed the full mechanism, based on which, the introduction of one equivalent base in the amidation is showcased here that a high yield (∼95 %) can be afforded using only 1.1 equiv. of amine. Abstract : Solving the puzzle : The role of the amine in direct amidation of aromatic ketones has been investigated. Amines act as both the reactant and catalyst, as such the excess amount (two or more equivalents) of amines are required to afford reasonable conversions/yields in the classical amidation. The direct amidation of aromatic ketones has been achieved at mild reaction conditions.